Evaluation of a Gait Assessment Module Using 3D Motion Capture Technology - Baskwill, MSc, BEd, RMT, Amanda J.; Belli, RMT, Patricia; Kelleher, PhD, Leila (International Journal of Therapeutic Massage & Bodywork, 2017)
Background: Gait analysis is the study of human locomotion. In massage therapy, this observation is part of an assessment process that informs treatment planning. Massage therapy students must apply the theory of gait assessment to simulated patients. At Humber College, the gait assessment module traditionally consists of a textbook reading and a three-hour, in-class session in which students perform gait assessment on each other. In 2015, Humber College acquired a three dimensional motion capture system. Purpose: The purpose was to evaluate the use of 3D motion capture in a gait assessment module compared to the traditional gait assessment module. Participants: Semester 2 massage therapy students who were enrolled in Massage Theory 2 (n = 38). Research Design: Quasi-experimental, wait-list comparison study. Intervention: The intervention group participated in an in-class session with a Qualisys motion capture system. Main Outcome Measure(s): The outcomes included knowledge and application of gait assessment theory as measured by quizzes, and students’ satisfaction as measured through a questionnaire. Results: There were no statistically significant differences in baseline and post-module knowledge between both groups (pre-module: p = .46; postmodule: p = .63). There was also no difference between groups on the final application question (p = .13). The intervention group enjoyed the in-class session because they could visualize the content, whereas the comparison group enjoyed the interactivity of the session. The intervention group recommended adding the assessment of gait on their classmates to their experience. Both groups noted more time was needed for the gait assessment module. Conclusions: Based on the results of this study, it is recommended that the gait assessment module combine both the traditional in-class session and the 3D motion capture system.